Crustal structure of the Moon determined from short-period Rayleigh wave analysis - Corchete, Victor (Frontiers in Astronomy and Space Sciences, 2025)
The lunar crustal structure is determined to be in a depth range of 0 to 40 km by means of Rayleigh wave analysis. The traces of three moonquakes were used to obtain Rayleigh wave dispersion (group velocities) in the short period range (fundamental mode: 0.5–12.5 s, first mode: 0.5–5.5 s, and second mode: 1–4 s). These moonquakes were registered by two stations placed on the Moon during the Apollo program. The dispersion was calculated with a combination of filtering techniques and was later inverted to the fundamental-mode dispersion to obtain an S-velocity model—an S-velocity distribution with depth. The S-velocity increased with depth, and a rapid S-velocity gradient was observed from 0 to 5 km in depth, while the S-velocity gradient became smaller down to 5 km in depth. While the present S-velocity model contributes to lunar crustal structure determination, more research is needed to precisely determine this structure, which will be possible when higher-quality data are acquired in future missions. Plain language summary: A rapid S-velocity gradient was determined from 0 to 5 km in depth. The low S-velocities (<2 km/s) determined for the first layers (0–2 km-depth) can be associated with the presence of broken and fractured materials at the uppermost lunar strata. The S-velocity increases with depth, but its gradient becomes slower deeper than 5 km.